Preface (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
The 2nd international conference Rehabilitation and Health Promotion: Future Perspectives, which will take place in Kaunas, Lithuania, on 16–17 April 2026, brings together researchers, clinicians, and policymakers to explore current challenges and future directions in rehabilitation sciences and health promotion. In the context of rapid demographic changes, increasing prevalence of chronic diseases, and ongoing technological advancements, there is a growing need for innovative, interdisciplinary, and evidence-based approaches to improve health outcomes and quality of life.This conference provides a platform for sharing scientific knowledge and practical experience across a wide range of topics. In the field of rehabilitation, particular attention is given to innovations in rehabilitation techniques, multidisciplinary approaches, and the integration of technology into clinical practice. The conference also addresses rehabilitation across the lifespan, including paediatric and geriatric populations, as well as condition-specific rehabilitation, sports injury recovery, mental health rehabilitation, and community-based approaches. Furthermore, issues related to chronic illness management, pain, and rehabilitation policy are explored, emphasising the need for patient-centred and sustainable solutions.In the domain of health promotion, the conference highlights strategies and interventions aimed at preventing chronic diseases and enhancing wellbeing. Key themes include mental health promotion, nutrition and physical activity, health promotion across the lifespan, and the use of digital technologies to support healthier lifestyles. The conference also emphasises the importance of health equity, social justice, and global perspectives, addressing the needs of diverse and vulnerable populations. Environmental and policy-related aspects of health promotion are also considered essential components of sustainable public health development.By fostering interdisciplinary dialogue and collaboration, the conference aims to contribute to the advancement of scientific knowledge and the development of innovative practices in rehabilitation and health promotion. Contributions from researchers at all career stages, including doctoral students and early-career scientists, are highly encouraged.We hope that the discussions and insights generated during this conference will inspire new research, strengthen international partnerships, and support the development of effective, inclusive, and forward-looking approaches to health and rehabilitation.